Railway axles

The railway axle design with specific chemical compositions and controlled dislocation density and lattice strain in both mating and central parallel portions effectively addresses fretting fatigue and enhances fatigue strength, improving the axle's durability under stress.

CN116194601BActive Publication Date: 2024-12-20NIPPON STEEL CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180065561.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-09-28
Publication Date
2024-12-20
Estimated Expiration
2041-09-28

AI Technical Summary

Technical Problem

Existing railway axles suffer from both fretting fatigue at the mating portions and fatigue failure at the central parallel portions, with prior art focusing primarily on suppressing fretting fatigue without addressing the fatigue strength of the central parallel portions.

Method used

A railway axle design with a mating portion and a central parallel portion, both featuring hardened layers formed through high-frequency quenching, with specific chemical compositions and controlled dislocation density and lattice strain to enhance fatigue strength, as defined by the formula (-4.8×10^16 × B + 8.5×10^16) / ρ ≥ 1.00, where ρ is the dislocation density and B is the half-value width of the (211) diffraction plane.

Benefits of technology

The railway axle exhibits improved fretting fatigue resistance at the mating portions and enhanced fatigue strength at the central parallel portions, stabilizing the axle's overall performance under repeated stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116194601B_ABST
    Figure CN116194601B_ABST
Patent Text Reader

Abstract

A railway axle (1) is provided, which has: a mating portion (2) in which fretting fatigue is suppressed, and a central parallel portion (3) showing excellent fatigue strength. The railway axle (1) disclosed in the present invention has: a pair of mating portions (2) for pressing into a railway wheel, comprising a mating portion hardened layer (2H) and a base material portion (BM); and a central parallel portion (3) arranged between the pair of mating portions (2), comprising a central parallel portion hardened layer (3H) and a base material portion (BM), wherein the base material portion (BM) is composed of a chemical composition described in the specification, and in a region of the central parallel portion hardened layer (3H) having a Vickers hardness of 480 HV or more, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m ‑2 Below, the half-value width B of the (211) diffraction plane is less than 1.34, and the dislocation density ρ and the half-value width B of the (211) plane based on X-ray diffraction satisfy the formula (1). (-4.8×10 16 ×B+8.5×10 16 ) / ρ≥1.00(1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an axle, and more particularly to a railway axle used in a railway vehicle. Background Art

[0002] The railway axle has a pair of mating parts for pressing into the railway wheel and a central parallel part arranged between the pair of mating parts. When in use, the railway axle supports the weight of the railway vehicle. Specifically, the interference fit of the mating part of the railway axle is set in a manner that the hole diameter of the hub part of the railway wheel is slightly smaller than the diameter of the mating part of the railway axle. Whenever the railway vehicle passes through a curved track (curved passage), the railway axle is also subjected to a horizontal force caused by the contact between the railway wheel and the track. That is, when passing through a curve, the railway axle is repeatedly subjected to rotational bending stress each time the railway wheel rotates. Moreover, the amplitude of the bending stress increases when passing through a curve.

[0003] As described above, in a railway axle, the mating portion for pressing into the railway wheel has a contact surface pressure relative to the hole of the hub portion of the railway wheel. Therefore, the mating portion of the railway wheel sometimes repeatedly undergoes slight slippage due to contact with the railway wheel. Hereinafter, slight slippage caused by contact between the mating portion of the railway wheel and the railway wheel is also referred to as micromotion. It is known that the mating portion of a railway axle is sometimes damaged by micromotion (hereinafter also referred to as "micromotion fatigue").

[0004] In order to suppress this fretting fatigue, high-frequency quenching is sometimes performed on the above-mentioned mating part of the railway axle. In the surface layer of the mating part, the hardness increases in the area that has been subjected to high-frequency quenching. Therefore, the area in the surface layer of the mating part whose hardness increases due to high-frequency quenching is called a "hardened layer". Compressive residual stress is generated in the hardened layer. The compressive residual stress generated by the hardened layer will suppress cracks caused by fretting. That is, the hardened layer of the railway axle formed by high-frequency quenching can suppress the fretting fatigue of the railway axle.

[0005] Japanese Patent Application Laid-Open No. 10-8202 (Patent Document 1), Japanese Patent Application Laid-Open No. 11-279696 (Patent Document 2), and Japanese Patent Application Laid-Open No. 2000-73140 (Patent Document 3) propose railway axles that are subjected to high-frequency quenching to suppress fretting fatigue at mating portions.

[0006] The railway axle disclosed in Patent Document 1 contains, by mass%, C: 0.3-0.48%, Si: 0.05-1%, Mn: 0.5-2%, Cr: 0.5-1.5%, Mo: 0.15-0.3%, and Ni: 0-2.4%. The mating portion of the railway axle has a hardened layer with a Vickers hardness of 400 or more, and has a martensite or bainite region inside. In the railway axle, the depth of the hardened layer is 1-4.5 mm. Patent Document 1 states that the railway axle has a high fatigue limit.

[0007] The railway axle disclosed in Patent Document 2 contains, by mass%, C: 0.3-0.48%, Si: 0.05-1%, Mn: 0.5-2%, Cr: 0.5-1.5%, Mo: 0.15-0.3% and Ni: 0-2.4%. The mating portion of the railway axle has a hardened layer with a Vickers hardness of 400 or more, and has a tempered martensite or bainite region inside. In the railway axle, the depth of the hardened layer is 5.0 mm or more and is 10% or less of the diameter of the mating portion. Patent Document 2 states that the railway axle has a high fretting fatigue limit.

[0008] The railway axle disclosed in Patent Document 3 contains C: 0.3-0.48%, Si: 0.05-1%, Mn: 0.5-2%, Cr: 0-1.5%, Mo: 0-0.3%, Ni: 0-2.4% by mass%. The mating end of the railway axle and its surrounding area have a hardened layer with a Vickers hardness of 400 or more. The ratio (K / D) of the thickness (K) of the hardened layer to the diameter (D) of the mating portion is 0.005-0.05. The upper part of the hardened layer contains 0.02-2% B. Patent Document 3 states that the railway axle has an excellent fatigue limit.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 10-8202

[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 11-279696

[0013] Patent Document 3: Japanese Patent Application Publication No. 2000-73140

[0014] Patent Document 4: Japanese Patent Application Publication No. 2007-321190

[0015] Non-patent literature

[0016] Non-patent document 1: Fumiaki Ikuta and four others, "Deformation and residual stress in high-frequency quenching of ring-shaped test pieces", Heat Treatment, Japan Heat Treatment Technology Association, February 2011, Vol. 55, No. 1, pp. 37-43 Summary of the invention

[0017] Problem that the invention aims to solve

[0018] The railway axles disclosed in Patent Documents 1 to 3 disclose a technique of suppressing fretting fatigue of a mating portion by performing high frequency quenching. As described above, when the mating portion of the railway axle is subjected to high frequency quenching to form a hardened layer, fretting fatigue of the mating portion can be suppressed.

[0019] However, in order to improve the fatigue strength of a railway axle, it is desirable to reduce not only fretting fatigue but also fatigue failure of the central parallel portion. However, the above-mentioned Patent Documents 1 to 3 do not study the fatigue strength of the central parallel portion of a railway axle.

[0020] An object of the present disclosure is to provide a railway axle having a mating portion in which fretting fatigue is suppressed and a central parallel portion that exhibits excellent fatigue strength.

[0021] Solutions for solving problems

[0022] The railway axle disclosed in the present invention comprises:

[0023] a pair of mating portions for pressing into a railway wheel; and

[0024] The central parallel portion is disposed between the pair of matching portions.

[0025] The aforementioned matching portion includes:

[0026] A mating portion hardened layer formed on the surface of the mating portion; and

[0027] The base material portion is located inside the hardened layer of the mating portion.

[0028] The aforementioned central parallel portion comprises:

[0029] a central parallel portion hardened layer formed on the surface of the central parallel portion; and

[0030] The aforementioned base material portion is located inside the aforementioned central parallel portion hardened layer.

[0031] The aforementioned base material portion is expressed in mass %

[0032] C: 0.22~0.29%,

[0033] Si: 0.15-0.40%,

[0034] Mn: 0.50~0.80%,

[0035] P: 0.020% or less,

[0036] S: 0.040% or less,

[0037] Cr: 0.90~1.20%,

[0038] Mo: 0.15-0.30%,

[0039] N: 0.0200% or less,

[0040] O: 0.0040% or less,

[0041] Ca: 0~0.0010%,

[0042] Cu: 0-0.30%,

[0043] Ni: 0-0.30%,

[0044] Al: 0~0.100%,

[0045] V: 0~0.060%、

[0046] Ti: 0~0.020%,

[0047] Nb: 0~0.030%,

[0048] B: 0 to 0.0050%, and

[0049] Balance: Fe and impurities,

[0050] In the region with a Vickers hardness of 480 HV or more in the central parallel portion hardened layer, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 the following,

[0051] The half-value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is less than 1.34 degrees.

[0052] The dislocation density ρ obtained based on the Co—Kα characteristic X-ray diffraction result and the half-value width B of the (211) diffraction plane based on the Co—Kα characteristic X-ray diffraction satisfy the formula (1).

[0053] (-4.8×10 16 ×B+8.5×10 16 ) / ρ≥1.00 (1)

[0054] Wherein, ρ in formula (1) is m -2The dislocation density obtained based on the Co-Kα characteristic X-ray diffraction result is substituted, and B is substituted in degrees for the half-value width of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction.

[0055] Effects of the Invention

[0056] The railway axle disclosed in the present invention has a mating portion in which fretting fatigue is suppressed and a central parallel portion that exhibits excellent fatigue strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 It is a side view of the railway axle according to the present embodiment.

[0058] Figure 2 yes Figure 1 The railway axle 1 of the present embodiment shown is a cross-sectional view taken along a plane including the central axis C1.

[0059] Figure 3 is a cross-sectional view of a rough product in this example.

[0060] Figure 4 It is a side view of the railway axle in this embodiment.

[0061] Figure 5 It is a schematic diagram of a fatigue testing device for a railway axle 1 in this embodiment.

[0062] Figure 6 is a cross-sectional view of the test material used in this example.

[0063] Figure 7 This is a cross-sectional view of a fatigue test piece used in this example. DETAILED DESCRIPTION

[0064] The inventors investigated and studied a method for improving the fatigue strength of the central parallel portion of a railway axle that forms a hardened layer (hereinafter referred to as "matching portion hardened layer") on the surface of the matching portion by high-frequency quenching to suppress fretting fatigue of the matching portion. As a result, the following findings were obtained.

[0065] (A) Chemical composition

[0066] If the central parallel portion of the railway axle is subjected to high frequency quenching, a hardened layer (hereinafter also referred to as "central parallel portion hardened layer") is formed on the surface of the central parallel portion. It is believed that if the central parallel portion hardened layer can be formed, the hardness of the surface of the central parallel portion is improved, and the fatigue strength of the central parallel portion is improved. Therefore, the inventors first conducted a detailed study on the chemical composition that can sufficiently improve the fatigue strength of the central parallel portion on the premise of forming the central parallel portion hardened layer.

[0067] As a result, it is believed that if the chemical composition of the base material part inside the central parallel part hardened layer in the railway axle is C: 0.22-0.29%, Si: 0.15-0.40%, Mn: 0.50-0.80%, P: 0.020% or less, S: 0.040% or less, Cr: 0.90-1.20%, Mo: 0.15-0.30%, N: 0.0200% or less, O: 0.00 When the content of Fe: 40% or less, Ca: 0-0.0010%, Cu: 0-0.30%, Ni: 0-0.30%, Al: 0-0.100%, V: 0-0.060%, Ti: 0-0.020%, Nb: 0-0.030%, B: 0-0.0050%, and the remainder: Fe and impurities, there is a possibility of improving the fatigue strength of the central parallel portion having a central parallel portion hardened layer formed by high-frequency quenching.

[0068] Next, the inventors of the present invention subjected the steel material formed into the shape of the railway axle having the above chemical composition to high-frequency quenching and tempering, thereby manufacturing various railway axles having a mating portion hardened layer and a central parallel portion hardened layer. As a result, the inventors of the present invention found that even if the railway axle has a base material portion having the above chemical composition and the surface hardness of the central parallel portion is the same, the fatigue strength of the central parallel portion may be different. That is, the inventors of the present invention have made it clear through their research that simply increasing the hardness of the central parallel portion hardened layer cannot sufficiently increase the fatigue strength of the central parallel portion.

[0069] (B) Regarding dislocation density

[0070] The inventors of the present invention believe that the reason why the fatigue strength of the central parallel portion is different even if the base material part of the railway axle that has been subjected to high-frequency quenching has the above-mentioned chemical composition and the surface hardness is the same is that the thermal history based on high-frequency quenching and tempering may have brought some influence. Therefore, the inventors of the present invention focused on the dislocation density and investigated and studied the method of improving the fatigue strength of the central parallel portion. Specifically, the inventors of the present invention defined the area with a Vickers hardness of 480 HV or more in the hardened layer of the central parallel portion as a "specific hardness area" and investigated and studied the dislocation density in the specific hardness area.

[0071] Wherein, in the specific hardness area formed by implementing high frequency quenching, the Vickers hardness is more than 480HV, and the hardness is very high, so the dislocation density is easy to become high. On the other hand, in the microstructure in the steel material under stress repeated load, dislocation moves and gathers, and it is possible to become the starting point of crack. That is, there is a tendency that dislocation is easy to gather and fatigue strength is easy to reduce in the specific hardness area with high dislocation density. Therefore, if the dislocation density is reduced in the specific hardness area with high dislocation density, it is difficult to cause the dislocation to gather to form the starting point of crack, and therefore, fatigue strength is likely to improve.

[0072] Based on the above findings, the inventors conducted detailed studies and found that if the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction results in the central parallel portion of the hardened layer having the above chemical composition is reduced to 2.5×10 16 m -2 Next, it is possible to improve the fatigue strength of the central parallel portion on the basis of satisfying the conditions of other features of the present embodiment. Therefore, in the central parallel portion of the railway axle of the present embodiment, the base material portion has the above chemical composition, and the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region is set to 2.5×10 16 m -2 the following.

[0073] (C) Regarding lattice strain

[0074] On the other hand, even if the central parallel portion has a base material portion and a central parallel portion hardened layer of the above chemical composition, and the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region of the central parallel portion hardened layer is 2.5×10 16 m -2 However, sometimes the fatigue strength cannot be fully improved. Therefore, the inventors of the present invention continue to focus on lattice strain and investigate and study methods to improve the fatigue strength of the central parallel portion. Among them, if the (211) diffraction plane is among the multiple diffraction planes obtained by X-ray diffraction (XRD: X-Ray Diffraction), the change of the lattice c-axis caused by the solid solution and precipitation of carbon (C) caused by high-frequency quenching and tempering can be observed. Therefore, the inventors of the present invention focus on the half-value width of the (211) diffraction plane as an indicator of the lattice strain in a specific hardness area, and investigate and study its relationship with the fatigue strength of the central parallel portion.

[0075] As mentioned above, in the microstructure of steel subjected to repeated stress loads, dislocations move and aggregate, which may become the starting point of cracks. On the other hand, the specific hardness area is formed by implementing high-frequency quenching. Among them, high-frequency quenching will cause phase change in the microstructure of the steel, so it can be considered that in the microstructure of the steel subjected to high-frequency quenching, microscopic strain occurs in the lattice. In areas where the microscopic strain of the lattice is locally large, there is a possibility that dislocations that move due to stress are easily retained. As a result, in areas with large lattice strain, due to the aggregation of dislocations, it is possible to become the starting point of cracks.

[0076] Based on the above findings, the inventors of the present invention have conducted detailed research, and the results show that, for the central parallel portion of the matrix portion and the central parallel portion hardened layer having the above chemical composition, if the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction in the specific hardness region is reduced to less than 1.34 degrees, it is possible to improve the fatigue strength of the central parallel portion on the basis of satisfying the conditions of other characteristics of the present embodiment. Therefore, in the central parallel portion of the railway axle of the present embodiment, the matrix portion has the above chemical composition, and the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region is set to 2.5×10 16 m -2 Hereinafter, the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is set to 1.34 degrees or less.

[0077] The inventors of the present invention conducted further detailed research and the results showed that if the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result and the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction satisfy the following formula (1), the fatigue strength of the central parallel portion can be stably improved.

[0078] (-4.8×10 16 ×B+8.5×10 16 ) / ρ≥1.00 (1)

[0079] Wherein, ρ in formula (1) is m -2 The dislocation density obtained based on the Co-Kα characteristic X-ray diffraction result is substituted, and B is substituted in degrees for the half-value width of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction.

[0080] Define Fn1 = (-4.8 × 10 16 ×B+8.5×10 16 ) / ρ. Fn1 is an index indicating the degree of dislocation aggregation in a specific hardness region. When Fn1 is less than 1.00, dislocations aggregate in a specific hardness region where stress is repeatedly applied, and become the starting point of cracks. As a result, the fatigue strength of the central parallel portion cannot be fully obtained. If Fn1 is greater than 1.00, dislocation aggregation can be suppressed even in a specific hardness region where stress is repeatedly applied, and the fatigue strength of the central parallel portion is improved.

[0081] The present inventors consider the following reasons. As described above, the central parallel portion of the matrix portion and the central parallel portion hardened layer having the above-mentioned chemical composition may cause dislocation movement due to repeated stress, which may cause cracks. That is, if not only the dislocation density is reduced, but also the densification of dislocations, cracking or slip can be suppressed, it is possible to improve the fatigue strength of the central parallel portion. Therefore, in the specific hardness region where the dislocation density is likely to increase, the railway axle of this embodiment is set to 2.5×10 16 m -2 Hereinafter, the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is set to 1.34 degrees or less, and Fn1 is set to 1.00 or more. As a result, the inventors believe that a balance between dislocation density and lattice strain can be achieved, and the fatigue strength of the central parallel portion can be improved.

[0082] Therefore, for the railway axle of the present embodiment, in the base material portion having the above chemical composition and the central parallel portion hardened layer, the dislocation density ρ in the specific hardness region obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 Hereinafter, the half width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction is 1.34 degrees or less, and the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result and the half width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction satisfy the formula (1). As a result, the railway axle of the present embodiment has excellent fatigue strength in the central parallel portion.

[0083] The gist of the railway axle according to the present embodiment completed based on the above findings is as follows. [1]

[0085] A railway axle, comprising:

[0086] a pair of mating portions for pressing into a railway wheel; and

[0087] The central parallel portion is disposed between the pair of matching portions.

[0088] The aforementioned matching portion includes:

[0089] A mating portion hardened layer formed on the surface of the mating portion; and

[0090] The base material portion is located inside the hardened layer of the mating portion.

[0091] The aforementioned central parallel portion comprises:

[0092] a central parallel portion hardened layer formed on the surface of the central parallel portion; and

[0093] The aforementioned base material portion is located inside the aforementioned central parallel portion hardened layer.

[0094] The aforementioned base material portion is expressed in mass %

[0095] C: 0.22~0.29%,

[0096] Si: 0.15-0.40%,

[0097] Mn: 0.50~0.80%,

[0098] P: 0.020% or less,

[0099] S: 0.040% or less,

[0100] Cr: 0.90~1.20%,

[0101] Mo: 0.15-0.30%,

[0102] N: 0.0200% or less,

[0103] O: 0.0040% or less,

[0104] Ca: 0~0.0010%,

[0105] Cu: 0-0.30%,

[0106] Ni: 0-0.30%,

[0107] Al: 0~0.100%,

[0108] V: 0~0.060%、

[0109] Ti: 0~0.020%,

[0110] Nb: 0~0.030%,

[0111] B: 0 to 0.0050%, and

[0112] Balance: Fe and impurities,

[0113] In the region with a Vickers hardness of 480 HV or more in the central parallel portion hardened layer, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 the following,

[0114] The half-value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is less than 1.34 degrees.

[0115] The dislocation density ρ obtained based on the Co—Kα characteristic X-ray diffraction result and the half-value width B of the (211) diffraction plane based on the Co—Kα characteristic X-ray diffraction satisfy the formula (1).

[0116] (-4.8×10 16 ×B+8.5×10 16 ) / ρ≥1.00 (1)

[0117] Wherein, ρ in formula (1) is m -2 The dislocation density obtained based on the Co-Kα characteristic X-ray diffraction result is substituted, and B is substituted in degrees for the half-value width of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction. [2]

[0119] The railway axle according to [1], wherein:

[0120] The aforementioned base material portion contains, by mass%, selected from

[0121] Cu: 0.01-0.30%,

[0122] Ni: 0.01~0.30%,

[0123] Al: 0.005~0.100%,

[0124] V: 0.005~0.060%,

[0125] Ti: 0.002~0.020%,

[0126] Nb: 0.002-0.030%, and

[0127] B: One or more elements selected from the group consisting of 0.0003 to 0.0050%.

[0128] Next, the railway axle according to the present embodiment will be described in detail.

[0129] [Structure of railway axles]

[0130] Figure 1 2 is a side view of a railway axle according to the present embodiment. Figure 1 The railway axle 1 of this embodiment includes a pair of engagement portions 2A and 2B and a central parallel portion 3. The pair of engagement portions 2A and 2B have diameters D W The central axis of the mating parts 2A and 2B coincides with the central axis C1 of the railway axle 1. The central axis C1 of the railway axle 1 extends along the longitudinal direction of the railway axle 1. In the following description, the "central axis C1 direction" of the railway axle 1 has the same meaning as the "longitudinal direction" of the railway axle 1.

[0131] The mating portion 2A is Figure 1 The matching portion 2B is connected to the left end of the central parallel portion 3. Figure 1 The right end of the central parallel portion 3 is connected to the middle. In the following description, the engaging portions 2A and 2B are collectively referred to as "engaging portions 2". In each engaging portion 2, a railway wheel (not shown) is press-fitted.

[0132] The central parallel portion 3 is disposed between the pair of matching portions 2A and 2B. Figure 1 In the figure, the left end of the central parallel portion 3 is connected to the mating portion 2A arranged on the left part of the railway axle 1. The right end of the central parallel portion 3 is connected to the mating portion 2B arranged on the right part of the railway axle 1. The central parallel portion 3 has a diameter D A The diameter D of the central parallel portion 3 A Smaller than the diameter D of the mating part 2 W The central axis of the central parallel portion 3 coincides with the central axis C1 of the railway axle 1. In short, the central parallel portion 3 and the pair of mating portions 2 are coaxially arranged.

[0133] The pair of mating parts 2 can be solid or hollow. Similarly, the central parallel part 3 can be solid or hollow. The diameter D of the central parallel part A There is no particular limitation, but it is, for example, 100 to 200 mm. W There is no particular limitation, but for example, it is 110 to 260 mm.

[0134] Reference Figure 1 The railway axle 1 also includes a tapered portion 4 between the end of the central parallel portion 3 and the inner end of the mating portion 2, which continuously connects the central parallel portion 3 and the mating portion 2. The diameter of the tapered portion 4 increases from the end of the central parallel portion 3 toward the inner end of the mating portion 2 in the direction of the central axis C1 of the railway axle 1. Figure 1 As shown, in the cross section including the central axis C1 of the railway axle 1, the surface of the tapered portion 4 may be either a curve or a straight line. It should be noted that the railway axle 1 may not have the tapered portion 4. In this case, the end of the central parallel portion 3 is connected to the inner end of the mating portion 2, and a height difference is formed between the end of the central parallel portion 3 and the inner end of the mating portion 2.

[0135] Figure 2 yes Figure 1 The cross-sectional view of the railway axle 1 according to the present embodiment shown in FIG. Figure 2 Each mating portion 2 (2A and 2B) includes a mating portion hardened layer 2H formed on the surface and a base material portion BM located inside the mating portion hardened layer 2H. The mating portion hardened layer 2H is formed in the surface layer ranging from the surface of the mating portion 2 to a predetermined depth.

[0136] Reference Figure 2 , the mating portion hardened layer 2H may not be formed on the entire surface of the mating portion 2. Figure 2 In the embodiment, the mating portion hardened layer 2H is formed on a part of the area outside the center position of the mating portion 2 and a part of the area inside the center position of the mating portion 2 in the direction of the center axis C1 of the railway axle 1, and the mating portion hardened layer 2H is not formed in the area including a part of the center position of the mating portion 2. Thus, the mating portion hardened layer 2H may not be formed on the entire surface of the mating portion 2, but may be formed on at least a part of the surface of the mating portion 2 in the direction of the center axis C1. In addition, the mating portion hardened layer 2H may be formed on the entire surface of the mating portion 2. The mating portion hardened layer 2H will be described later.

[0137] Reference Figure 2 The central parallel portion 3 includes: a central parallel portion hardened layer 3H formed on the surface layer of the central parallel portion 3, and a base material portion BM located inside the central parallel portion hardened layer 3H. The central parallel portion hardened layer 3H is formed in the surface layer ranging from the surface of the central parallel portion 3 to a predetermined depth. The central parallel portion hardened layer 3H is formed on the entire surface of the central parallel portion 3. The central parallel portion hardened layer 3H will be described later.

[0138] [Regarding the Chemical Composition of the Matrix Part BM of the Central Parallel Part 3]

[0139] In the present embodiment, the chemical composition of the base material BM of the pair of mating portions 2 and the chemical composition of the base material BM of the central parallel portion 3 contain the following elements. In the cross section perpendicular to the central axis C1 of the railway axle 1, the line segment connecting the surface of the railway axle 1 and the central axis C1 is defined as the radius R. In this case, the chemical composition of the base material BM refers to the chemical composition at the R / 2 position of the mating portion 2 and the R / 2 position of the central parallel portion 3. In the following, the % of an element refers to mass % unless otherwise specified.

[0140] C: 0.22~0.29%

[0141] Carbon (C) increases the hardness of steel. C also increases the hardness of the hardened layer formed by high-frequency quenching. If the C content is less than 0.22%, even if the contents of other elements are within the range of the present embodiment, the hardness of the base material part BM, the mating part hardened layer 2H and the central parallel part hardened layer 3H will decrease. As a result, the fatigue strength of the central parallel part 3 is sometimes reduced. On the other hand, if the C content exceeds 0.29%, even if the contents of other elements are within the range of the present embodiment, quenching cracks sometimes occur during high-frequency quenching. Therefore, the C content is 0.22 to 0.29%. The preferred lower limit of the C content is 0.23%, and more preferably 0.24%. The preferred upper limit of the C content is 0.28%, and more preferably 0.27%.

[0142] Si: 0.15-0.40%

[0143] Silicon (Si) deoxidizes steel. Si also increases the temper softening resistance of steel and improves the fatigue strength of the central parallel portion 3. If the Si content is less than 0.15%, these effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Si content exceeds 0.40%, quenching cracks sometimes occur during high-frequency quenching even if the contents of other elements are within the range of the present embodiment. Therefore, the Si content is 0.15 to 0.40%. The preferred lower limit of the Si content is 0.20%, more preferably 0.23%, and more preferably 0.25%. The preferred upper limit of the Si content is 0.37%, more preferably 0.35%, and more preferably 0.33%.

[0144] Mn: 0.50~0.80%

[0145] Manganese (Mn) improves the hardenability of steel and thickens the hardened layers 2H and 3H formed by high-frequency quenching. If the Mn content is less than 0.50%, even if the contents of other elements are within the range of the present embodiment, the central parallel portion hardened layer 3H may become too thin. In this case, the fatigue strength of the central parallel portion 3 cannot be fully obtained. On the other hand, if the Mn content exceeds 0.80%, even if the contents of other elements are within the range of the present embodiment, the mating portion hardened layer 2H and the central parallel portion hardened layer 3H may become too thick. In this case, the compressive residual stress of the mating portion hardened layer 2H is reduced, and the fatigue strength of the mating portion 2 cannot be fully obtained. Therefore, the Mn content is 0.50 to 0.80%. The preferred lower limit of the Mn content is 0.55%, more preferably 0.57%, more preferably 0.60%, and more preferably 0.62%. The preferred upper limit of the Mn content is 0.78%, more preferably 0.75%, more preferably 0.73%, and more preferably 0.70%.

[0146] P: 0.020% or less

[0147] Phosphorus (P) is an impurity that is inevitably contained. That is, the P content is greater than 0%. P segregates at the grain boundaries and reduces the fatigue strength of the steel. If the P content exceeds 0.020%, the fatigue strength of the railway axle 1 will be reduced even if the contents of other elements are within the range of the present embodiment. Therefore, the P content is less than 0.020%. The preferred upper limit of the P content is 0.018%, more preferably 0.016%, more preferably 0.015%, and more preferably 0.014%. The P content is preferably as low as possible. However, an extreme reduction in the P content will significantly increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the P content is 0.001%, and more preferably 0.002%.

[0148] S: 0.040% or less

[0149] Sulfur (S) is an impurity that is inevitably contained. That is, the S content is greater than 0%. S combines with Mn to form MnS. MnS reduces the fatigue strength of steel. If the S content exceeds 0.040%, even if the contents of other elements are within the range of this embodiment, stress is concentrated on MnS, resulting in a decrease in the fatigue strength of the central parallel portion 3. Therefore, the S content is less than 0.040%. The preferred upper limit of the S content is 0.030%, more preferably 0.020%, more preferably 0.015%, and more preferably 0.010%. The S content is preferably as low as possible. However, an extreme reduction in the S content will significantly increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the S content is 0.001%, and more preferably 0.002%.

[0150] Cr: 0.90~1.20%

[0151] Chromium (Cr) improves the hardenability of steel and increases the hardness of the mating portion hardened layer 2H and the central parallel portion hardened layer 3H formed by high-frequency quenching. If the Cr content is less than 0.90%, the central parallel portion hardened layer 3H sometimes becomes too thin. In this case, the fatigue strength of the central parallel portion 3 is reduced. On the other hand, if the Cr content exceeds 1.20%, even if the contents of other elements are within the range of the present embodiment, the mating portion hardened layer 2H and the central parallel portion hardened layer 3H sometimes become too thick. In this case, the compressive residual stress of the mating portion hardened layer 2H is reduced, and sufficient fatigue strength of the mating portion 2 cannot be obtained. Therefore, the Cr content is 0.90 to 1.20%. The preferred lower limit of the Cr content is 0.95%, more preferably 1.00%, more preferably 1.02%, and more preferably 1.05%. The preferred upper limit of the Cr content is 1.19%, more preferably 1.17%, and more preferably 1.15%.

[0152] Mo: 0.15~0.30%

[0153] Molybdenum (Mo) increases the strength of steel. If the Mo content is less than 0.15%, even if the contents of other elements are within the range of the present embodiment, the effect cannot be fully obtained. On the other hand, if the Mo content exceeds 0.30%, even if the contents of other elements are within the range of the present embodiment, the above effects are saturated. When the Mo content exceeds 0.30%, it will also lead to excessive increase in manufacturing costs. Therefore, the Mo content is 0.15 to 0.30%. The preferred lower limit of the Mo content is 0.17%, more preferably 0.19%, more preferably 0.20%, and more preferably 0.21%. The preferred upper limit of the Mo content is 0.29%, more preferably 0.28%, and more preferably 0.27%.

[0154] N: 0.0200% or less

[0155] Nitrogen (N) is inevitably contained. That is, the N content is greater than 0%. N combines with Al and the like to form fine nitrides, which refines the grains. However, if the N content is too high, coarse nitrides are formed and the fatigue strength of the steel is reduced. If the N content exceeds 0.0200%, the fatigue strength of the railway axle 1 will be reduced even if the contents of other elements are within the range of the present embodiment. Therefore, the N content is below 0.0200%. The preferred upper limit of the N content is 0.0150%, more preferably 0.0120%, more preferably 0.0100%, more preferably 0.0090%, more preferably 0.0080%, and more preferably 0.0070%. In order to more effectively obtain the above-mentioned effect, the preferred lower limit of the N content is 0.0010%, more preferably 0.0020%, and more preferably 0.0030%.

[0156] O: 0.0040% or less

[0157] Oxygen (O) is an impurity that is inevitably contained. That is, the O content is greater than 0%. O sometimes generates coarse oxides, which become the starting point of fatigue failure. If the O content exceeds 0.0040%, even if the content of other elements is within the range of this embodiment, the fatigue strength of the central parallel portion 3 will be reduced. Therefore, the O content is below 0.0040%. The preferred upper limit of the O content is 0.0030%, more preferably 0.0025%, more preferably 0.0020%, and more preferably 0.0015%. The O content is preferably as low as possible. However, an extreme reduction in the O content will significantly increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the O content is 0.0001%, more preferably 0.0002%, and more preferably 0.0005%.

[0158] Ca: 0~0.0010%.

[0159] Calcium (Ca) is an impurity. Ca may not be contained. That is, the Ca content may be 0%. Ca causes silicate inclusions (group C specified in JIS G0555 (2003)) to condense, resulting in a decrease in the fatigue strength of the steel. If the Ca content exceeds 0.0010%, even if the contents of other elements are within the range of the present embodiment, silicate inclusions will become the starting point of fatigue failure, and the fatigue strength of the central parallel portion 3 will decrease. Therefore, the Ca content is 0 to 0.0010%. The preferred upper limit of the Ca content is 0.0006%, more preferably 0.0004%, and more preferably 0.0003%.

[0160] The balance of the chemical composition of the base material BM of the mating portion 2 and the central parallel portion 3 of the railway axle 1 of the present embodiment is Fe and impurities. Here, impurities refer to substances mixed from ore, scraps, or the manufacturing environment as raw materials when the steel material of the railway axle 1 is industrially manufactured, and are permissible substances within a range that does not adversely affect the railway axle 1 of the present embodiment.

[0161] The chemical composition of the base material part BM of the mating portion 2 and the central parallel portion 3 of the railway axle 1 of the present embodiment may further contain one or more elements selected from the group consisting of Cu and Ni in place of a portion of Fe. These elements are optional elements and all increase the strength of steel.

[0162] Cu: 0-0.30%.

[0163] Copper (Cu) is an optional element and may not be contained. That is, the Cu content may be 0%. When Cu is contained, Cu improves the strength of the steel. As long as a small amount of Cu is contained, this effect can be obtained to a certain extent. However, if the Cu content exceeds 0.30%, the hot workability of the steel will decrease even if the contents of other elements are within the scope of the present embodiment. Therefore, the Cu content is 0 to 0.30%. The preferred lower limit of the Cu content exceeds 0%, more preferably 0.01%, and more preferably 0.02%. The preferred upper limit of the Cu content is 0.25%, more preferably 0.20%, more preferably 0.15%, more preferably 0.10%, and more preferably 0.05%.

[0164] Ni: 0~0.30%

[0165] Nickel (Ni) is an optional element and may not be contained. That is, the Ni content can be 0%. When Ni is contained, Ni improves the strength of the steel. As long as a small amount of Ni is contained, this effect can be obtained to a certain extent. However, if the Ni content exceeds 0.30%, the above effect is saturated even if the content of other elements is within the scope of this embodiment. Therefore, the Ni content is 0 to 0.30%. The preferred lower limit of the Ni content exceeds 0%, more preferably 0.01%, more preferably 0.02%, and more preferably 0.04%. The preferred upper limit of the Ni content is 0.25%, more preferably less than 0.20%, more preferably 0.15%, and more preferably 0.10%.

[0166] The chemical composition of the base material portion BM of the mating portion 2 and the central parallel portion 3 of the railway axle 1 of the present embodiment may further contain Al in place of a portion of Fe.

[0167] Al: 0~0.100%

[0168] Aluminum (Al) is an optional element and may not be contained. That is, the Al content may be 0%. When Al is contained, Al deoxidizes the steel. Al further combines with N to form AlN, which refines the grains. As a result, the toughness of the steel is improved. As long as a small amount of Al is contained, these effects can be obtained to a certain extent. However, if the Al content exceeds 0.100%, even if the content of other elements is within the range of the present embodiment, coarse oxide inclusions are generated, resulting in a decrease in the fatigue strength of the railway axle 1. Therefore, the Al content is 0 to 0.100%. The preferred lower limit of the Al content exceeds 0%, more preferably 0.005%, more preferably 0.007%, more preferably 0.010%, more preferably 0.015%, and more preferably 0.020%. The preferred upper limit of the Al content is 0.080%, more preferably 0.060%, more preferably 0.050%, more preferably 0.045%, and more preferably 0.040%. In this specification, the Al content refers to the content of acid-soluble Al (sol.Al).

[0169] The chemical composition of the base material BM of the mating portion 2 and the central parallel portion 3 of the railway axle 1 of the present embodiment may further contain one or more elements selected from the group consisting of V, Ti and Nb in place of a portion of Fe. These elements are optional elements and all increase the strength of steel.

[0170] V: 0~0.060%

[0171] Vanadium (V) is an optional element and may not be contained. That is, the V content may be 0%. When V is contained, V combines with N and C to form V (C, N). In this case, the grains are refined and the strength of the steel is improved. As long as a small amount of V is contained, this effect can be obtained to a certain extent. However, if the V content exceeds 0.060%, the toughness of the steel will decrease even if the contents of other elements are within the range of this embodiment. Therefore, the V content is 0 to 0.060%. The preferred lower limit of the V content exceeds 0%, more preferably 0.005%, more preferably 0.008%, and more preferably 0.010%. The preferred upper limit of the V content is 0.055%, more preferably 0.050%, more preferably 0.045%, and more preferably 0.040%.

[0172] Ti: 0~0.020%

[0173] Titanium (Ti) is an optional element and may not be contained. That is, the Ti content can be 0%. When Ti is contained, Ti combines with N to form fine TiN. TiN increases the strength of steel. TiN further refines the grains and improves the fatigue strength of steel. As long as a small amount of Ti is contained, this effect can be obtained to a certain extent. However, if the Ti content exceeds 0.020%, even if the content of other elements is within the range of this embodiment, the TiN precipitates will become the path of cracks, resulting in a decrease in the toughness of the steel. Therefore, the Ti content is 0 to 0.020%. The preferred lower limit of the Ti content exceeds 0%, more preferably 0.002%, and more preferably 0.003%. The preferred upper limit of the Ti content is 0.018%, more preferably 0.015%, more preferably 0.013%, more preferably 0.010%, and more preferably 0.007%.

[0174] Nb: 0~0.030%

[0175] Niobium (Nb) is an optional element and may not be contained. That is, the Nb content may be 0%. When Nb is contained, Nb combines with N and C to form Nb (C, N). In this case, Nb (C, N) refines the grains and improves the strength and toughness of the steel. As long as a small amount of Nb is contained, this effect can be obtained to a certain extent. However, if the Nb content exceeds 0.030%, even if the content of other elements is within the range of this embodiment, the carbides and / or carbonitrides generated in the steel may sometimes coarsen. In this case, the toughness of the steel will decrease instead. Therefore, the Nb content is 0 to 0.030%. The preferred lower limit of the Nb content exceeds 0%, more preferably 0.002%, more preferably 0.003%, and more preferably 0.005%. The preferred upper limit of the Nb content is 0.029%, more preferably 0.027%, more preferably 0.025%, and more preferably 0.020%.

[0176] The chemical composition of the base material portion BM of the mating portion 2 and the central parallel portion 3 of the railway axle 1 of the present embodiment may further contain B in place of a portion of Fe.

[0177] B: 0~0.0050%

[0178] Boron (B) is an optional element and may not be contained. That is, the B content may be 0%. When B is contained, B improves the hardenability of the steel. As long as a small amount of B is contained, this effect can be obtained to a certain extent. On the other hand, if the B content exceeds 0.0050%, the toughness of the steel will decrease even if the contents of other elements are within the scope of the present embodiment. Therefore, the B content is 0 to 0.0050%. The preferred lower limit of the B content exceeds 0%, more preferably 0.0003%, more preferably 0.0005%, and more preferably 0.0007%. The preferred upper limit of the B content is 0.0040%, more preferably 0.0030%, and more preferably 0.0020%.

[0179] [About the microstructure of the base material BM]

[0180] In the railway axle 1 of the present embodiment, the microstructure of the base material part BM is preferably composed mainly of martensite and bainite. In this specification, "composed mainly of martensite and bainite" means that the total area ratio of martensite and bainite in the microstructure is 80% or more. Among them, martensite also includes tempered martensite. Bainite includes tempered bainite.

[0181] The remainder other than martensite and bainite in the microstructure of the base material portion BM of the railway axle 1 of the present embodiment is, for example, ferrite. The microstructure of the base material portion BM of the railway axle 1 corresponds to the microstructure of the surface portion of the railway axle before high-frequency quenching. If the microstructure of the base material portion BM of the railway axle 1 is mainly composed of martensite and bainite, the hardness of the surface portion of the railway axle 1 is improved. If the microstructure is mainly composed of martensite and bainite, the microstructure of the surface portion will also be rapidly austenitized during high-frequency heating. In this case, the martensite fraction of the hardened layer formed by high-frequency quenching is increased, and the hardness of the hardened layer is increased. As a result, the fatigue strength of the railway axle 1 after high-frequency quenching is further improved.

[0182] The total area ratio of martensite and bainite in the microstructure of the base material part BM of the railway axle 1 can be calculated by the following method. Collect 5 samples for microstructure observation from the R / 2 position of the cross section perpendicular to the center axis C1 direction of the fitting part 2 or the central parallel part 3. The cross section perpendicular to the center axis C1 is used as the observation surface. After the observation surface of each sample is polished into a mirror surface, it is immersed in a nitric acid alcohol etching solution for about 10 seconds to reveal the microstructure by etching. Observe the etched observation surface with an optical microscope. Each field of view is set to 40000μm 2 (magnification: 500 times), and one field of view was observed for each sample (ie, a total of 5 fields of view were observed using 5 samples).

[0183] In each field of view, martensite and bainite, as well as phases other than martensite and bainite (ferrite, etc.) are determined based on contrast. Martensite and bainite are difficult to distinguish by contrast. However, martensite and bainite can be easily distinguished from phases other than martensite and bainite, such as ferrite, based on contrast. Based on the total area of ​​martensite and bainite determined and the area of ​​each field of view (40000μm 2 ), and the total area ratio of martensite and bainite in each field of view was calculated. The arithmetic mean of the total area ratios of martensite and bainite calculated in each field of view was defined as the total area ratio (%) of martensite and bainite.

[0184] [About the Fitting Part Hardened Layer 2H and the Center Parallel Part Hardened Layer 3H]

[0185] The railway axle 1 of the present embodiment has a mating portion hardened layer 2H formed on each of a pair of mating portions 2. The railway axle 1 of the present embodiment also has a central parallel portion hardened layer 3H formed on the central parallel portion 3. In this specification, "hardened layer" refers to a region formed by high-frequency quenching and having a higher Vickers hardness than the base material portion BM. Specifically, in this specification, the mating portion hardened layer 2H and the central parallel portion hardened layer 3H are defined as: a region with a limit hardness of 350 HV in Vickers hardness as specified as the effective hardened layer depth in JIS G 0559 (2008). In short, in this specification, the limit hardness of the mating portion hardened layer 2H and the central parallel portion hardened layer 3H is 350 HV in Vickers hardness.

[0186] [About the microstructure of the mating part hardened layer 2H and the central parallel part hardened layer 3H]

[0187] The railway axle 1 of this embodiment preferably has a microstructure of the mating portion hardened layer 2H and the central parallel portion hardened layer 3H mainly composed of martensite and bainite. In this specification, "mainly composed of martensite and bainite" means that the total area ratio of martensite and bainite in the microstructure is 80% or more. Among them, martensite also includes tempered martensite. Bainite includes tempered bainite.

[0188] The total area ratio of martensite and bainite in the microstructure of the mating portion hardened layer 2H and the central parallel portion hardened layer 3H of the railway axle 1 can be calculated in the same manner as the total area ratio of martensite and bainite in the microstructure of the base material portion BM of the railway axle 1 of the present embodiment. Specifically, 5 samples for observing the microstructure are collected from the mating portion hardened layer 2H and / or the central parallel portion hardened layer 3H determined by the above method. The cross section perpendicular to the central axis C1 is used as the observation surface. After the observation surface of each sample is polished into a mirror surface, it is immersed in a nitric acid alcohol etching solution for about 10 seconds, and the microstructure is revealed by etching. The etched observation surface is observed with an optical microscope. Each field of view is set to 40000μm 2 (magnification: 500 times), and one field of view was observed for each sample (ie, a total of 5 fields of view were observed using 5 samples).

[0189] [About specific hardness range]

[0190] In this embodiment, the region of the central parallel portion hardened layer 3H having a Vickers hardness of 480 HV or more is defined as a "specific hardness region". As described above, the limit hardness of the central parallel portion hardened layer 3H is 350 HV in Vickers hardness. That is, the specific hardness region refers to a region of the central parallel portion hardened layer 3H having a particularly high hardness.

[0191] In the present embodiment, the specific hardness region can be determined by the following method. The load is set to 2.9N, and the central parallel portion hardened layer 3H of the present embodiment is subjected to a Vickers hardness test according to JIS Z2244 (2009) at a spacing of 0.1mm to measure the Vickers hardness (HV). For example, it can be cut perpendicularly to the central axis C1 of the railway axle 1, and the Vickers hardness (HV) of the obtained surface is measured from the surface of the central parallel portion 3 along the radial direction (depth direction) of the railway axle 1. Based on the hardness transition curve obtained in this way, an area with a Vickers hardness of 480HV or more is determined from the surface of the railway axle 1. The determined area with a Vickers hardness of 480HV or more is defined as a specific hardness region.

[0192] [About dislocation density]

[0193] In the railway axle 1 of the present embodiment, in the region of the central parallel portion hardened layer 3H having a Vickers hardness of 480 HV or more, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 As described above, the region with a Vickers hardness of 480 HV or more in the central parallel portion hardened layer 3H of the present embodiment is referred to as a specific hardness region. In the present embodiment, the dislocation density ρ in the specific hardness region of the central parallel portion hardened layer 3H obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 the following.

[0194] As described above, the specific hardness region is a region with particularly high hardness in the central parallel portion hardening layer 3H. Therefore, the dislocation density in the specific hardness region tends to be high. On the other hand, dislocations move in the steel material under repeated stress and may become the starting point of cracks. That is, it is believed that the higher the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result, the easier it is for the starting point of cracks to be generated, and the easier it is for the fatigue strength to be reduced. Therefore, in the railway axle 1 of this embodiment, in the central parallel portion hardening layer 3H, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region is set to 2.5×10 16 m -2 As a result, the central parallel portion 3 has excellent fatigue strength while satisfying the other characteristic conditions of the railway axle 1 according to the present embodiment.

[0195] In this embodiment, the upper limit of the dislocation density ρ in the specific hardness region of the central parallel portion hardened layer 3H obtained based on the Co-Kα characteristic X-ray diffraction result is preferably 2.4×10 16 m -2It should be noted that the lower limit of the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region of the central parallel portion hardened layer 3H is not particularly limited. However, if the dislocation density is too low, it is sometimes impossible to obtain a Vickers hardness of 480 HV or more defined as a specific hardness region. Therefore, in this embodiment, the lower limit of the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region of the central parallel portion hardened layer 3H is, for example, 1.4×10 16 m -2 .

[0196] The dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the railway axle 1 of the present embodiment can be obtained by the following method. From the central parallel portion 3 of the railway axle 1 of the present embodiment, a specific hardness area is determined by the above method. A test piece for measuring the dislocation density is made from the specific hardness area. The size of the test piece is not particularly limited, for example, it is 10 mm circumferentially × 20 mm axially × 5 mm radially relative to the railway axle 1. The thickness direction of the test piece is the radial direction (depth direction) of the railway axle 1. In this case, the observation surface of the test piece is a surface of 10 mm circumferentially × 20 mm axially relative to the railway axle 1.

[0197] The observation surface of the test piece is mechanically ground and further electrolytically ground to remove the strain of the surface. For the observation surface after electrolytic grinding, a diffraction curve is obtained based on the X-ray diffraction method (XRD). In XRD, the ray source is set to CoKα line, the tube voltage is set to 30kV, and the tube current is set to 100mA. In addition, the diffraction angle (2θ) is set to a range of 45 to 105 degrees, and the measurement is performed at a pitch of 0.02 degrees and 0.6 seconds per point. It should be noted that the correction of the peak position corresponding to the diffraction angle can be performed by using a Si standard plate to confirm whether the diffraction peak position of a specific surface deviates from the reference position. In addition, for the half-value width, LaB6 (lanthanum hexaboride) is used as a standard sample and the width of the device is measured in advance.

[0198] Based on the obtained diffraction curves, the peak position (2θ) and half-value width (B') of the (110), (211) and (220) diffraction planes are respectively calculated. Based on the peak position (2θ) of each diffraction plane, the half-value width (B') of each diffraction plane and the Williamson-Hall formula (Formula (2)), the inhomogeneous strain ε is calculated.

[0199] B'×cosθ / λ=0.9 / D+2ε×sinθ / λ (2)

[0200] In formula (2), θ represents the diffraction angle, λ represents the wavelength of X-ray (0.1788965 nm), and D is the crystallite diameter.

[0201] More specifically, based on the peak position (2θ) of each diffraction surface and the half-value width (B') of each diffraction surface, B'×cos(θ) / λ and sin(θ) / λ are calculated. For each (110), (211) and (220) diffraction surface, the obtained B'×cos(θ) / λ is plotted on the vertical axis and sin(θ) / λ is plotted on the horizontal axis, and a straight line is obtained by curve fitting. The inhomogeneous strain ε is obtained based on the slope (2ε) of the obtained straight line. Based on the obtained ε, the Burgers vector b and the following formula (3), the dislocation density ρ (m -2 ).

[0202] ρ=14.4×ε 2 / b 2 (3)

[0203] In formula (3), b represents the Burgers vector (0.25 nm) of the body-centered cubic structure (iron).

[0204] [About the half-value width of the (211) diffraction surface]

[0205] In the railway axle 1 of the present embodiment, in the region where the Vickers hardness of the central parallel portion hardened layer 3H is 480 HV or more, the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction is 1.34 degrees or less. As described above, the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction is an indicator of the microscopic strain of the lattice.

[0206] As described above, the specific hardness region has a particularly high hardness in the central parallel portion hardened layer 3H, and the dislocation density is likely to increase. Therefore, as described above, in this embodiment, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region is reduced to 2.5×10 16 m -2 However, even if the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction results in the specific hardness region is reduced to 2.5×10 16 m -2 In the region where the microscopic strain of the crystal lattice is locally increased, dislocations tend to be easily retained due to repeated stress. Therefore, the railway axle 1 of the present embodiment reduces the microscopic strain of the crystal lattice in the specific hardness region of the central parallel portion hardened layer 3H.

[0207] Therefore, in the central parallel portion 3 of the railway axle 1 of the present embodiment, the base material portion has the above chemical composition, and the dislocation density ρ in the specific hardness region of the central parallel portion hardened layer 3H obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×1016 m -2 Below, the half-value width B of the (211) diffraction surface based on the Co-Kα characteristic X-ray diffraction is less than 1.34 degrees. In the present embodiment, the preferred upper limit of the half-value width B of the (211) diffraction surface based on the Co-Kα characteristic X-ray diffraction in the specific hardness region of the central parallel portion hardened layer 3H is 1.33 degrees, and more preferably 1.32 degrees. It should be noted that in the specific hardness region of the central parallel portion hardened layer 3H, the lower limit of the half-value width B of the (211) diffraction surface based on the Co-Kα characteristic X-ray diffraction is not particularly limited. In the present embodiment, the lower limit of the half-value width B of the (211) diffraction surface based on the Co-Kα characteristic X-ray diffraction in the specific hardness region of the central parallel portion hardened layer 3H is, for example, 0.9 degrees.

[0208] In the railway axle 1 of the present embodiment, the half-width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction can be obtained by the following method. A test piece is prepared under the same conditions as those for obtaining the dislocation density ρ based on the Co-Kα characteristic X-ray diffraction result, and a diffraction curve is obtained by XRD under the same conditions as those for obtaining the dislocation density ρ based on the Co-Kα characteristic X-ray diffraction result. The peak of the (211) diffraction plane is determined from the obtained diffraction curve, and its half-width is obtained. The obtained half-width is defined as the half-width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction.

[0209] [About formula (1)]

[0210] For the railway axle 1 of the present embodiment, in the region where the Vickers hardness of the central parallel portion hardened layer 3H is 480 HV or higher, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction results and the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction satisfy equation (1).

[0211] (-4.8×10 16 ×B+8.5×10 16 ) / ρ≥1.00 (1)

[0212] Wherein, ρ in formula (1) is m -2 The dislocation density obtained based on the Co-Kα characteristic X-ray diffraction result is substituted, and B is substituted in degrees for the half-value width of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction.

[0213] Fn1(=(-4.8×10 16 ×B+8.5×10 16) / ρ) is an index indicating the degree of dislocation aggregation in a specific hardness region. When Fn1 is less than 1.00, dislocations aggregate in a specific hardness region where stress is repeatedly applied, and become the starting point of cracks. As a result, the fatigue strength of the central parallel portion cannot be fully obtained. However, if Fn1 is above 1.00, dislocation aggregation can be suppressed even in a specific hardness region where stress is repeatedly applied, and the fatigue strength of the central parallel portion can be improved.

[0214] Therefore, in the central parallel portion 3 of the railway axle 1 of the present embodiment, the base material portion has the above chemical composition, and the dislocation density ρ in the specific hardness region of the central parallel portion hardened layer 3H obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 Hereinafter, the half-value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is 1.34 degrees or less, and Fn1 is 1.00 or more. In the present embodiment, the preferred lower limit of Fn1 is 1.01, and more preferably 1.03. In the present embodiment, the upper limit of Fn1 is not particularly limited. In the present embodiment, the upper limit of Fn1 is, for example, 3.0.

[0215] [Manufacturing method]

[0216] An example of a method for manufacturing a railway axle according to the present embodiment will be described.

[0217] Molten steel having the above chemical composition is manufactured. A steel ingot is manufactured using the molten steel. The steel ingot is subjected to hot forging to manufacture a rough product having an axle shape. The heating temperature of the steel ingot during hot forging may be within a known temperature range. The heating temperature is, for example, 1000 to 1300° C. The manufactured rough product is subjected to quenching and tempering treatment, or normalizing treatment.

[0218] When quenching and tempering are performed, the upper limits of quenching and tempering can be known conditions. Specifically, the quenching temperature in the quenching process is set to A c3 The rough product is kept at the quenching temperature and then rapidly cooled by water cooling or oil cooling. The tempering temperature is set to A during the tempering treatment. c1 Below the phase transformation point. Keep the rough product at the tempering temperature and then cool it naturally. In the case of normalizing, c1 The raw product is kept at the heat treatment temperature of the phase transformation point and then naturally cooled. It should be noted that tempering treatment may also be performed after normalizing treatment.

[0219] The rough product that has been subjected to quenching and tempering or normalizing treatment is subjected to machining as needed. Thereafter, the rough product is subjected to high-frequency quenching and tempering treatment. The high-frequency quenching and tempering treatment are described in detail below.

[0220] [About high frequency quenching treatment]

[0221] In high frequency quenching, high frequency heating is used to make the surface of the rough product reach a ratio of A c3 The rough product is cooled after reaching a temperature with a high transformation point. In this case, the surface layer of the rough product transforms from austenite to martensite or bainite. As a result, a hardened layer is formed on the surface layer of the rough product.

[0222] The high-frequency quenching treatment can be performed using a known high-frequency heating device and a known cooling device. For example, as the high-frequency heating device, a ring-shaped high-frequency heating device can be used, and as the cooling device, a ring-shaped cooling device can be used. In this case, by arranging the center axis C1 of the railway axle 1 coaxially with the ring-shaped high-frequency heating device and the ring-shaped cooling device, the high-frequency quenching treatment can be efficiently performed on the surfaces of the mating portion 2 and the central parallel portion 3 of the railway axle 1.

[0223] The high-frequency quenching treatment of this embodiment can heat the surface layer of the rough product to A by high-frequency heating. c3 The phase transition point or above is not particularly limited. That is, in the present embodiment, as high-frequency heating, a known high-frequency heating may be performed. For example, the frequency of the alternating current of the high-frequency heating device may be set to 1 to 10 kHz.

[0224] In the high-frequency quenching treatment of this embodiment, the cooling rate is appropriately controlled during cooling. If the cooling rate during quenching is too slow, the mating portion hardened layer 2H and the central parallel portion hardened layer 3H may not form a microstructure of martensite and bainite as the main body, and the hardness of the mating portion hardened layer 2H and the central parallel portion hardened layer 3H may not be sufficiently improved in the manufactured railway axle 1. Therefore, in the conventional high-frequency quenching, the cooling during high-frequency quenching is performed by rapid cooling. On the other hand, since the high-frequency heating is performed to a temperature higher than A, the high-frequency heating is used to heat the steel sheet to a temperature higher than A. c3 The temperature of the phase transformation point is the phase transformation point, so rapid cooling is accompanied by phase transformation. As a result, the faster the cooling rate, the higher the dislocation density after high-frequency quenching.

[0225] In the high-frequency quenching treatment of the present embodiment, only the surface layer of the rough product is heated and cooled. As a result, the manufactured railway axle 1 is formed with a mating portion hardened layer 2H, a central parallel portion hardened layer 3H and a base material portion BM. That is, in the high-frequency quenching treatment of the present embodiment, only a part of the rough product is heated and then rapidly cooled. Therefore, the high-frequency quenching of the present embodiment is easy to be cooled faster than the quenching in which the entire steel material is heated and then rapidly cooled using a heat treatment furnace or the like.

[0226] A specific example is given to explain the cooling rate when only the surface part is heated and then cooled by high-frequency quenching. Patent document 4 (Japanese Patent Publication No. 2007-321190) discloses a method for manufacturing a steel material with excellent fatigue properties. Paragraph

[0051] of patent document 4 states that it is preferred to set the cooling rate during high-frequency quenching to 200°C / second or more. More specifically, referring to paragraph

[0054] of patent document 4 and Tables 2-1 to 2-3, it is disclosed that when the depth of the hardened layer is set to about 2 to 7 mm, the cooling rate after the high-frequency quenching heating is maintained to 1000°C / second.

[0227] In addition, non-patent document 1 discloses a cooling rate in the range of 500 to 200°C in high-frequency quenching treatment. Specifically, Figures 13 to 15 recorded on page 5 of non-patent document 1 show the relationship between the time (seconds) from the start of heating and the temperature (°C) of the workpiece (heated material) in the high-frequency quenching treatment. Referring to Figures 13 to 15 of non-patent document 1, when the workpiece is cooled, the time taken to reach 200°C from 500°C is less than 2 seconds. That is, Figures 13 to 15 of non-patent document 1 show that in the high-frequency quenching treatment, the cooling rate in the range of 500 to 200°C is more than 150°C / second at multiple measurement points.

[0228] Therefore, the conventional high-frequency quenching treatment is to perform rapid cooling at a very fast cooling rate. The high-frequency quenching treatment of the present embodiment controls the cooling rate from 500°C before reaching the Ms point to 200°C after passing the Mf point, and adjusts it to avoid the dislocation density ρ becoming too high. Specifically, in the high-frequency quenching treatment of the present embodiment, the cooling rate CR in the range of 500 to 200°C is reduced to less than 80°C / second. As a result, in the specific hardness region of the hardened layer 3H of the central parallel portion of the manufactured railway axle 1, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result can be reduced to 2.5×10 16 m -2 the following.

[0229] The upper limit of the cooling rate CR in the range of 500 to 200°C is preferably 60°C / second, more preferably 50°C / second, and more preferably 40°C / second. On the other hand, as described above, if the cooling rate CR in the range of 500 to 200°C is too slow, a microstructure of martensite and bainite as the main body may not be formed. Therefore, in the high-frequency quenching treatment of the present embodiment, the lower limit of the cooling rate CR in the range of 500 to 200°C is, for example, 10°C / second.

[0230] It should be noted that the cooling rate CR in the range of 500 to 200° C. can be obtained by measuring the surface temperature of the crude product using a K-type thermocouple. In addition, the method for adjusting the cooling rate CR in the range of 500 to 200° C. is not particularly limited. For example, when the crude product is cooled by spray water cooling or mist water cooling, the cooling rate CR in the range of 500 to 200° C. can be adjusted by adjusting the amount of water sprayed or sprayed.

[0231] [About tempering]

[0232] In this embodiment, the rough product subjected to the high-frequency quenching treatment is subjected to the tempering treatment. During the tempering treatment, the precipitation of ε carbides, the recovery (disappearance) of dislocations, and the reduction of lattice strain occur in the microstructure of the rough product. That is, by performing the tempering treatment, the dislocation density ρ increased by the high-frequency quenching treatment and the half-value width B of the (211) plane in the X-ray diffraction can be reduced.

[0233] In the tempering treatment of the present embodiment, λ defined by the following formula (A) is set to 8600 to 10000.

[0234] λ=T(log 10 (t)+20)(A)

[0235] Wherein, T in formula (A) is substituted for the tempering temperature in K, and t is substituted for the tempering time in hours.

[0236] In this specification, the tempering temperature T (K) corresponds to the temperature (K) of the heat treatment furnace in which the tempering is performed. Also, in this specification, the tempering time corresponds to the time (hours) during which the railway axle 1 is kept at the tempering temperature T (K).

[0237] If λ is too small, it is sometimes impossible to sufficiently reduce the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result and / or the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction. If λ is too large, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is too low, and sometimes it is impossible to obtain a hardness of 480 HV or more in terms of Vickers hardness in the central parallel portion hardened layer 3H. Therefore, in the tempering treatment of the present embodiment, λ is set to 8600 to 10000. As a result, the railway axle 1 of the present embodiment can reduce the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result to 2.5×10 16 m -2 Below, and the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is set to 1.34 degrees or less.

[0238] The railway axle 1 of the present embodiment improves the fatigue strength of the central parallel portion 3 by achieving a balance between the dislocation density (i.e., the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result) and the lattice strain (i.e., the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction) in a specific hardness region of the central parallel portion hardened layer 3H. On the other hand, as described above, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result varies with the cooling rate in the range of 500 to 200°C during the high-frequency quenching treatment. In addition, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result and the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction vary with the tempering treatment λ. Therefore, a balance between the high-frequency quenching treatment and the tempering treatment is achieved in the present embodiment.

[0239] Specifically, in the induction hardening and tempering treatment of the present embodiment, F defined by the following formula (B) is set to 90,000 to 400,000.

[0240] F=CR×λ(B)

[0241] Here, CR in the formula (B) is substituted by the cooling rate in the range of 500 to 200° C. in° C. / sec, and λ is substituted by λ defined in the formula (A).

[0242] If F is too small, the half-value width B of the (211) diffraction surface based on the Co-Kα characteristic X-ray diffraction in the specific hardness region of the central parallel portion hardened layer 3H may become too high. If F is too large, Fn1 may be less than 1.00. Therefore, in this embodiment, F is set to 90000 to 400000. As a result, the railway axle 1 of this embodiment can reduce the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result to 2.5×10 16 m -2 Hereinafter, the half value width B of the (211) diffraction plane based on Co—Kα characteristic X-ray diffraction can be set to 1.34 degrees or less, and further, Fn1 can be set to 1.00 or more.

[0243] The rough product to which the tempering treatment has been applied is cooled to room temperature. In this case, the cooling after the tempering treatment is not particularly limited. For example, the rough product to which the tempering treatment has been applied can be naturally cooled to room temperature. The rough product to which the tempering treatment has been applied can also be further subjected to final mechanical processing. That is, mechanical processing is an optional processing step. It should be noted that, when mechanical processing is applied, mechanical processing (turning and grinding) is applied within a range that can ensure a hardened layer of the required depth. Through the above steps, the railway axle 1 of this embodiment can be manufactured.

[0244] The above-mentioned method for manufacturing the railway axle 1 is an example of the method for manufacturing the railway axle 1 of the present embodiment. Therefore, as long as the chemical composition of the base material BM of the mating portion 2 and the central parallel portion 3 is within the above-mentioned range, and the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result in the specific hardness region of the central parallel portion hardened layer 3H is 2.5×10 16 m -2 The railway axle 1 of the present embodiment in which the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is 1.34 degrees or less and Fn1 is 1.00 or more is not limited to the above-mentioned manufacturing method.

[0245] The effects of the railway axle 1 of the present embodiment will be described in more detail below through examples. The conditions in the following examples are one example of conditions used to confirm the feasibility and effects of the railway axle 1 of the present embodiment. Therefore, the railway axle 1 of the present embodiment is not limited to this one example of conditions.

[0246] Example 1

[0247] In Example 1, a railway axle 1 was manufactured, and the fatigue strength of the central parallel portion 3 was evaluated. Specifically, molten steel was manufactured, and the molten steel had a chemical composition of C: 0.26%, Si: 0.29%, Mn: 0.69%, P: 0.012%, S: 0.006%, Cr: 1.11%, Mo: 0.26%, N: 0.0036%, O: 0.0019%, Al: 0.032%, and the balance was Fe and impurities. A steel ingot was manufactured from the manufactured molten steel. The steel ingot was heated to 1250°C and hot forged to manufacture Figure 3 A rough product 10 in the shape of an axle is shown. Figure 3 2 is a cross-sectional view of a rough product in this embodiment. The rough product 10 includes a pair of engaging portions 20 and a central parallel portion 30 disposed between the pair of engaging portions 20 .

[0248] The rough product 10 of each test number was quenched and tempered. The heat treatment temperature during quenching was set to be higher than the A c3 The phase transformation point is 890°C. The raw product 10 is kept at the heat treatment temperature and then water quenched. The rough product 10 of each test number after quenching is tempered. As for the tempering conditions, the tempering temperature is adjusted at 550 to 670°C so that the rough product 10 of each test number has the same degree of surface hardness. The rough product 10 is kept at the tempering temperature for 120 minutes and then air-cooled to room temperature.

[0249] The tempered rough product 10 is subjected to high frequency quenching treatment. Figure 3The hatched area of ​​the rough product 10 shown in the figure is subjected to high-frequency quenching. The quenching temperature during high-frequency quenching is A of the steel of each test number. c3 Above the transformation point. For the rough product 10 of each test number, the cooling rate CR (°C / second) in the range of 500 to 200°C during high-frequency quenching is shown in Table 1. It should be noted that the cooling rate CR (°C / second) is measured using a K-type thermocouple. In addition, the adjustment of the cooling rate CR (°C / second) is performed by adjusting the amount of water during cooling.

[0250] [Table 1]

[0251] Table 1

[0252]

[0253] The rough product 10 of each test number subjected to high-frequency quenching was subjected to tempering treatment. The tempering temperature (°C) in the tempering treatment applied to the rough product 10 of each test number is shown as "T (°C)" and the tempering time is shown as "t (hours)" in Table 1. In addition, from the tempering temperature T (°C) in the tempering applied to the rough product 10 of each test number, the tempering time t (hours) and the above formula (A), λ (= (273 + T) × (log 10 (t))+20). The obtained λ of each test number is shown in Table 1. Furthermore, F (=CR×λ) was obtained from the cooling rate CR (°C / sec) in the range of 500 to 200°C when the rough product 10 of each test number was subjected to high-frequency quenching, λ during tempering, and the above formula (B). The obtained F of each test number is shown in Table 1.

[0254] The raw product 10 subjected to the high-frequency quenching treatment is subjected to mechanical processing to produce Figure 4 A railway axle 1 is shown. Figure 4 1 is a side view of a railway axle in this embodiment. The railway axle 1 of each test number has a pair of mating portions 2 and a central parallel portion 3. Each mating portion 2 has a width of 200 mm and a diameter D W The diameter D of the central parallel portion 3 is 150 mm. A The curvature radius of the fillet portion between the fitting portion 2 and the central parallel portion 3 is 10 mm. The railway axle 1 is manufactured through the above manufacturing steps.

[0255] [Evaluation test]

[0256] The manufactured railway axle 1 was subjected to the X-ray diffraction measurement test and fatigue test described below.

[0257] [X-ray diffraction measurement test]

[0258] A specific hardness region is determined from the hardened layer 3H of the central parallel portion of the railway axle 1 of each test number manufactured. A test piece for X-ray diffraction measurement test is made from the specific hardness region of the hardened layer 3H of the central parallel portion of each test number. The size of the test piece is 10mm circumferentially × 20mm axially × 5mm radially of the railway axle 1. The circumferential 10mm × axial 20mm is used as the observation surface, and the observation surface is mechanically polished and electrolytically polished, and the X-ray diffraction measurement is carried out by the above method. An X-ray diffraction device is used in the measurement, and the measurement conditions are set to CoKα characteristic X-rays, tube voltage 30kV, and tube current 100mA. The correction of the peak position corresponding to the diffraction angle is carried out by using a Si standard plate to confirm whether the diffraction peak position of the specific surface deviates from the reference position. In addition, for the half-value width, LaB6 (lanthanum hexaboride) is used as a standard sample and the device width is measured in advance.

[0259] From the obtained Co-Kα characteristic X-ray diffraction curve, the peak positions (2θ) and half-value widths (B') of the (110), (211), and (220) planes were determined, and the dislocation density ρ (10 16 m -2 The dislocation density ρ (10 16 m -2 ) are shown in Table 1 as “dislocation density ρ”.

[0260] From the obtained Co-Kα characteristic X-ray diffraction curve, the peak of the (211) diffraction plane was further determined, and its half-value width was calculated. The half-value width B (degrees) of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction for each test number is shown in Table 1 as "half-value width B (degrees)". Furthermore, in each test number, the dislocation density ρ (10 16 m -2 ), based on the half-value width B (degrees) of the (211) diffraction plane of Co-Kα characteristic X-ray diffraction and the above formula (1), Fn1 (= (-4.8×10 16 ×B+8.5×10 16 ) / ρ). The obtained Fn1 for each test number is shown in Table 1.

[0261] [Fatigue test]

[0262] Figure 5 Schematic diagram of a fatigue test device for a railway axle 1 in this embodiment. Figure 5A jig 200 equivalent to a wheel is pressed into the mating portion 2A on one side of the railway axle 1 of each test number. The jig 200 equivalent to the wheel is fixed. Thus, the railway axle 1 is cantilevered. A bending fatigue test is performed, and the inner side ( 700 mm from the inner side end of the mating portion 2A that has been fixed) of the railway axle 1 is 700 mm from the inner side end ( Figure 5 A load was repeatedly applied in a direction perpendicular to the center axis C1 direction of the railway axle 1 at a point P in the middle. As a testing machine, an electro-hydraulic servo fatigue testing machine (load capacity 500 kN) manufactured by Saginomiya Seisakusho was used.

[0263] The test conditions were set to an alternating load with a stress ratio of -1 and a frequency of 1 to 3 Hz. The number of repetitions was 5 × 10 6 The upper limit is 5×10 6 If the fracture does not occur after 5×10 6 The minimum value of the test stress for the first fracture is set as F B In addition, F B Below 5×10 6 The maximum value of the test stress without fracture is set as F M . M With F B The average value is set to F A , and (F B -F M ) / F A F when ≤0.10 A The fatigue limit of the test number 1-1 thus obtained is defined as the fatigue limit. The fatigue limit of the test number 1-1 is used as the test stress applied to the railway axle 1 of each test number.

[0264] The fatigue test was performed by applying the test stress determined as above (i.e., the fatigue limit of test number 1-1) to the railway axle 1 of each test number. The test conditions were the same as those described above, and the number of repetitions was 5×10 6 The upper limit is 5×10. 6 The railway axle 1 with the number of repetitions of 5×10 was evaluated as having excellent fatigue strength (“E” (Excellent) in Table 1). 6 The railway axle 1 that was broken was evaluated as not having excellent fatigue strength ("NA" (Not Acceptable) in Table 1). Table 1 shows the evaluation results of the fatigue test for each test number.

[0265] [Evaluation results]

[0266] Referring to Table 1, the dislocation density ρ of the railway axle 1 of test number 1-1 obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 The half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is 1.34 degrees or less, and Fn1 is 1.00 or more. As a result, the steel has excellent fatigue strength in a fatigue test.

[0267] On the other hand, the cooling rate CR (°C / sec) in the range of 500 to 200°C during induction hardening of the railway axle 1 of test number 1-2 was too high. Moreover, F in the induction hardening and tempering treatments was too high. As a result, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction results exceeded 2.5×10 16 m -2 As a result, it does not have excellent fatigue strength in fatigue tests.

[0268] The λ in the tempering condition of the railway axle 1 of test number 1-3 was too low. As a result, the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction exceeded 1.34 degrees. As a result, it did not have excellent fatigue strength in the fatigue test.

[0269] The railroad axle 1 of test number 1-4 had too high F in the high-frequency quenching and tempering treatments. As a result, Fn1 was less than 1.00. As a result, it did not have excellent fatigue strength in the fatigue test.

[0270] Example 2

[0271] In Example 2, a test piece simulating a railway axle 1 was prepared, and the fatigue strength of the central parallel portion was evaluated. Specifically, molten steel having the chemical composition described in Table 2 was manufactured. Among them, "-" in Table 2 means that the content of the corresponding element is at the impurity level. Specifically, "-" in the Cu, Ni, and V contents means that the content of each element is less than 0.01%. "-" in the Al content means that the Al content is less than 0.002%. "-" in the Ti and Nb contents means that the content of each element is less than 0.001%. "-" in the B and Ca contents means that the content of each element is less than 0.0001%.

[0272] [Table 2]

[0273]

[0274] Steel ingots were produced from the molten steel of Steel Nos. 1 to 8. For Steel No. 1, the steel ingot was heated to 1250° C. and then hot forged to produce Figure 3The rough product 10 of the axle shape shown in FIG. For steel Nos. 2 to 8, the steel ingots were heated to 1250°C and then hot forged to produce rough products of 180 mm in diameter and 300 mm in length. Figure 3 The diameter of the central parallel portion 30 of the axle shape shown in the figure is substantially the same. The rough product 10 of each steel number is quenched and tempered. The heat treatment temperature during quenching is set to be higher than the A of the steel. c3 The phase transformation point is 890°C. The raw product 10 is kept at the heat treatment temperature and then water quenched. The rough product 10 of each test number after quenching is tempered. As for the tempering conditions, the tempering temperature is adjusted at 550 to 670°C so that the rough product 10 of each test number has the same degree of surface hardness. The rough product 10 is kept at the tempering temperature for 120 minutes and then air-cooled to room temperature.

[0275] The test material of each test number was made from the rough product of each steel number. The test material 100 has Figure 6 Shape shown. Figure 6 is a cross-sectional view of the test material used in this embodiment. The test material 100 of each test number was subjected to high-frequency quenching. The high-frequency quenching was performed in such a way that a hardened layer was formed on the entire test material 100. The quenching temperature during the high-frequency quenching was A of the steel of each test number. c3 The cooling rate CR (°C / second) in the range of 500 to 200°C during high-frequency quenching is shown in Table 3. It should be noted that the cooling rate CR (°C / second) was measured using a K-type thermocouple. In addition, the cooling rate CR (°C / second) was adjusted by adjusting the amount of water during cooling.

[0276] [Table 3]

[0277] Table 3

[0278]

[0279] The test materials 100 of each test number subjected to induction hardening were tempered. The tempering temperature (°C) in the tempering performed on the test materials 100 of each test number is shown as "T (°C)" and the tempering time is shown as "t (hours)" in Table 3. In addition, from the tempering temperature T (°C) in the tempering performed on the test materials 100 of each test number, the tempering time t (hours) and the above formula (A), λ (= (273 + T) × (log 10 (t))+20). The obtained λ of each test number is shown in Table 3. Furthermore, F (=CR×λ) was obtained from the cooling rate CR (°C / sec) in the range of 500 to 200°C when the test material 100 of each test number was subjected to high-frequency quenching, λ during tempering, and the above formula (B). The obtained F of each test number is shown in Table 3. The test material 100 of each test number subjected to tempering was subjected to machining to produce Figure 7 The fatigue test piece 500 is shown. Figure 7 This is a cross-sectional view of a fatigue test piece used in this example.

[0280] [Evaluation test]

[0281] The fatigue test pieces 500 of the respective test numbers were subjected to the X-ray diffraction measurement test and fatigue test described below.

[0282] [X-ray diffraction measurement test]

[0283] From the fatigue test pieces 500 of each test number manufactured, test pieces for X-ray diffraction measurement test are made. The size of the test piece is 10 mm in the circumferential direction × 20 mm in the axial direction × 5 mm in the radial direction of the railway axle 1. The circumferential direction of 10 mm × 20 mm in the axial direction is used as the observation surface, and the observation surface is subjected to mechanical grinding and electrolytic grinding, and the X-ray diffraction measurement is carried out by the above method. An X-ray diffraction device is used in the measurement, and the measurement conditions are set to CoKα characteristic X-ray, tube voltage 30 kV, and tube current 100 mA. The correction of the peak position corresponding to the diffraction angle is carried out by using a Si standard plate to confirm whether the diffraction peak position of a specific surface deviates from the reference position. In addition, for the half-value width, LaB6 (lanthanum hexaboride) is used as a standard sample and the device width is measured in advance for correction.

[0284] From the obtained Co-Kα characteristic X-ray diffraction curve, the peak positions (2θ) and half-value widths (B') of the (110), (211), and (220) planes were determined, and the dislocation density ρ (10 16 m -2 The dislocation density ρ (10 16 m -2 ) is shown in Table 3 as "dislocation density ρ". From the obtained Co-Kα characteristic X-ray diffraction curve, the peak of the (211) diffraction plane is further determined, and its half-value width is calculated. The half-value width B (degrees) of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction of each test number is shown in Table 3 as "half-value width B (degrees)".

[0285] Furthermore, in each test number, the dislocation density ρ(10 16 m -2 ), based on the half-value width B (degrees) of the (211) diffraction plane of Co-Kα characteristic X-ray diffraction and the above formula (1), Fn1 (= (-4.8×10 16 ×B+8.5×10 16) / ρ). The Fn1 of each test number is shown in Table 3. It should be noted that, for test numbers 2-9, 2-10 and 2-11, in the preliminary test conducted in advance, almost no difference was observed from the X-ray diffraction curve shown in Table 1. Therefore, in test numbers 2-9, 2-10 and 2-11, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result, the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction, and Fn1 used the measured values ​​shown in Table 1.

[0286] [Fatigue test]

[0287] The fatigue test piece 500 of each test number was subjected to an Ono-type rotating bending fatigue test. The test frequency was set to 60 Hz, room temperature (25° C.) and in an atmosphere until the number of repetitions was 1×10 7 times. Near the fatigue limit, fatigue tests were carried out using multiple test pieces, and the fatigue limit was calculated according to the modified step method. The Vickers hardness was calculated for the cross section of the gripping portion of the fatigue test piece 500 of each test number. The pressing force was set to 9.8N, and the 5-point method (1 point in the center of the cross section and 4 points in the R / 2 portion) was used, and the measured average value was defined as the Vickers hardness (HV) of each test number. For each test number, the obtained fatigue limit (MPa) was divided by the Vickers hardness (HV) and defined as the standardized fatigue limit of each test number. The obtained standardized fatigue limit is shown in Table 3 as "Standardized Fatigue Limit".

[0288] [Evaluation results]

[0289] Referring to Table 2 and Table 3, the dislocation density ρ of the test materials 100 of test numbers 2-1 to 2-8 obtained based on the Co-Kα characteristic X-ray diffraction results is 2.5×10 16 m -2 The half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is 1.34 degrees or less, and Fn1 is 1.00 or more. As a result, the normalized fatigue limit is 1.50 or more, and the steel has excellent fatigue strength.

[0290] On the other hand, the cooling rate CR (°C / sec) of the test material 100 of test number 2-9 in the range of 500 to 200°C during induction hardening was too fast. Moreover, F in the induction hardening and tempering treatments was too high. As a result, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction results exceeded 2.5×10 16 m -2 As a result, the normalized fatigue limit was less than 1.50, and the steel did not have excellent fatigue strength.

[0291] The λ in the tempering condition of the test material 100 of test number 2-10 was too low. As a result, the half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction exceeded 1.34 degrees. As a result, the normalized fatigue limit was less than 1.50, and it did not have excellent fatigue strength.

[0292] In the test materials 100 of test numbers 2-11 and 2-12, F in the induction hardening and tempering treatment was too high. As a result, Fn1 was less than 1.00. As a result, the normalized fatigue limit was less than 1.50, and the excellent fatigue strength was not obtained.

[0293] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments may be appropriately modified and implemented without departing from the gist thereof.

[0294] Description of Reference Numerals

[0295] 1Railway axle

[0296] 2. Coordination

[0297] 3 central parallel part

[0298] 2H Hardened layer of mating part

[0299] 3H Central parallel hardened layer

[0300] BM Base Material Department

Claims

1. A railway axle, comprising: a pair of mating portions for pressing into a railway wheel; and a central parallel portion disposed between the pair of matching portions, The matching portion comprises: a mating portion hardening layer formed on a surface layer of the mating portion; and a base material portion which is located inside the hardened layer of the mating portion, The central parallel portion comprises: a central parallel portion hardened layer formed on a surface layer of the central parallel portion; and The base material portion is located inside the hardened layer of the central parallel portion. The matrix part is C in mass %: 0.22 to 0.29%, Si: 0.15-0.40%, Mn: 0.50~0.80%, P: 0.020% or less, S: 0.040% or less, Cr: 0.90~1.20%, Mo: 0.15-0.30%, N: 0.0200% or less, O: 0.0040% or less, Ca: 0~0.0010%, Cu: 0-0.30%, Ni: 0~0.30% Al: 0~0.100%, V: 0~0.060%、 Ti: 0~0.020%, Nb: 0~0.030%, B: 0 to 0.0050%, and Balance: Fe and impurities, In the region of the central parallel portion hardened layer having a Vickers hardness of 480 HV or more, the dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result is 2.5×10 16 m -2 The half value width B of the (211) diffraction plane based on Co-Kα characteristic X-ray diffraction is 1.34 degrees or less. The dislocation density ρ obtained based on the Co-Kα characteristic X-ray diffraction result and the half-value width B of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction satisfy the formula (1), (-4.8×10 16 ×B+8.5×1016 ) / ρ≥1.00 (1) in, The ρ in formula (1) is m -2 The dislocation density obtained based on the Co-Kα characteristic X-ray diffraction result is substituted, and B is substituted in degrees for the half-value width of the (211) diffraction plane based on the Co-Kα characteristic X-ray diffraction.

2. The railway axle according to claim 1, wherein: The base material portion contains, in terms of mass%, selected from Cu: 0.01-0.30%, Ni: 0.01~0.30%, Al:0.005~0.100%、 V:0.005~0.060%、 Ti: 0.002~0.020%, Nb: 0.002-0.030%, and B: One or more elements selected from the group consisting of 0.0003 to 0.0050%.